OGT as potential novel target: Structure, function and inhibitors. (25th April 2022) - Zhang, Ning; Jiang, Hongli; Zhang, Kexin; Zhu, Jiaxin; Wang, Zhongzhong; Long, Yiteng; He, Yanjun; Feng, Feng; Liu, Wenyuan; Ye, Feng; Qu, Wei
Abstract: O-linked N-acetylglucosamine transferase (OGT), a key protein in O-linked N-acetylglucosamine (O-GlcNAc) post-translational modification, catalyzes O-GlcNAcylation by linking GlcNAc from glycosyl donors to protein Ser/Thr residues to regulate multiple biological processes. OGT has become a popular research topic in the field of glycobiology as a potential target. This report consists of three parts, namely: the basic information of OGT, the relationship between OGT and diseases, and the research progress of OGT inhibitors. This report aims to improve the understanding of OGT-related fields from the perspective of its structure. OGT inhibitors could aid the effective and efficient investigation of the O-GlcNAcylation mechanism, and provide new ideas and methods for the treatment of related diseases. Highlights: Structure and function of OGT protein. Relationship between OGT protein and diseases. A comprehensive summary of the reported OGT inhibitors. Design ideas and directions of OGT inhibitors.